Occurrence and Biological Activities of Phenylpropionyl Iridoids - Cao, Jiaoxian; Yu, Hanchuan; Wu, Yingchun; Wang, Xinhong (Mini Reviews in Medicinal Chemistry, 2019)
As noteworthy members of the terpenoid family, iridoids are a group of natural compounds that have a cyclopentane ring and hemiacetal structural features. Among them, phenylpropionyl iridoids— widely present in Bignoniaceae, Rubiaceae, Scrophulariaceae, Verbenaceae, and Oleaceae— were discovered and extracted from plants mainly between the 1980s and 2000s. Because of their unique structural features and complex stereo configurations, these compounds exhibit numerous desirable biological activities such as neuroprotective, anti-inflammatory, antimicrobial, and antitumour activities; they have received increasing interest recently. This review summarises progress in research on phenylpropionyl iridoids, including their occurrence and biological activities.
Keywords: Phenylpropionyl iridoids